2013
DOI: 10.1093/her/cyt055
|View full text |Cite
|
Sign up to set email alerts
|

Adolescents' awareness of cancer risk factors and associations with health-related behaviours

Abstract: Increasing adolescents' awareness of the contribution of modifiable lifestyle factors to cancer risk may influence life-long patterns of healthy behaviour. However, little is known about adolescents' awareness of cancer risk factors and the effectiveness of awareness-raising interventions. This study assessed adolescents' cancer awareness and the effectiveness of an existing cancer-specific school-based intervention delivered by Teenage Cancer Trust. The Cancer Awareness Measure was completed by 478 adolescent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
56
1
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 41 publications
(67 citation statements)
references
References 19 publications
9
56
1
1
Order By: Relevance
“…Cancer Similar findings have been reported in a controlled study in four UK schools, where the authors assessed the effectiveness of an educational intervention delivered by Teenage Cancer Trust [25]. Besides, fairly similar awareness of lung cancer risk factors was observed among both British and Colombian adolescents [25]; while higher levels of awareness have been found in German high school students, 92% of the German scholars identified smoking as a risk factor for lung cancer [26].…”
Section: Awareness Of Warning Signs and Risk Factors For Lungsupporting
confidence: 75%
See 1 more Smart Citation
“…Cancer Similar findings have been reported in a controlled study in four UK schools, where the authors assessed the effectiveness of an educational intervention delivered by Teenage Cancer Trust [25]. Besides, fairly similar awareness of lung cancer risk factors was observed among both British and Colombian adolescents [25]; while higher levels of awareness have been found in German high school students, 92% of the German scholars identified smoking as a risk factor for lung cancer [26].…”
Section: Awareness Of Warning Signs and Risk Factors For Lungsupporting
confidence: 75%
“…Besides, fairly similar awareness of lung cancer risk factors was observed among both British and Colombian adolescents [25]; while higher levels of awareness have been found in German high school students, 92% of the German scholars identified smoking as a risk factor for lung cancer [26]. The present educational intervention raised female scholars' awareness on lung cancer prevention through healthy lifestyles.…”
Section: Awareness Of Warning Signs and Risk Factors For Lungsupporting
confidence: 69%
“…Awareness of the skin cancer-related risk factor ‘getting sunburnt more than once as a child’ was assessed alongside 10 other cancer risk factors on a five-point Likert scale. In accordance with previous practice,21 25 responses were dichotomised for analysis (ie, mole: ‘yes’ vs ‘no’/‘don't know’; sunburn: ‘strongly agree’/‘agree’ vs ‘not sure’/‘disagree’/‘strongly disagree’).…”
Section: Methodsmentioning
confidence: 99%
“…Only one UK study to date has examined the association between sunscreen and sunbed use and cancer awareness, which found that female adolescents who used sunbeds were statistically significantly more likely to agree that UV exposure was a cancer risk factor 21. Moreover, patterns of sun-related behaviours (ie, sunbathing and sunburn) and protective practices (ie, sunscreen use) and tanning attitudes among Scottish adolescents have not previously been described.…”
Section: Introductionmentioning
confidence: 99%
“…In fact, it is more common to associate a cancer diagnosis to an older person than to a young person [8], especially in developed countries where aging populations are fuelling the burden of cancer [1,2,[9][10][11]. However, aging is not the only factor associated with cancer: more than half of the deaths from cancer are attributed to unhealthy behaviour options [12], which frequently are shaped during adolescence, like tobacco consumption [13]. Adolescents and young adults are thus preferential targets for cancer prevention education because they are in the age of active learning.…”
Section: The Potential Of Youth For Primary Prevention Of Cancermentioning
confidence: 99%